Depressive symptoms are associated with hippocampal neurodegeneration in preclinical autosomal dominant Alzheimer's disease: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Gatchel, Jennifer R.; Lopera, Francisco; Fox‐Fuller, Joshua T.; Guzman‐Velez, Edmarie; Bocanegra, Yamile; Pardilla‐Delgado, Enmanuelle; Vila‐Castelar, Clara; Schoemaker, Dorothee; Baena, Ana; Torrico‐Teave, Heirangi; Munera, Diana; Vannini, Patrizia; et al.
Abstract: Background: Increasing evidence suggests that depressive symptoms may be among early behavioral changes in Alzheimer's Disease (AD). However, the neurobiology of these symptoms in the preclinical stages of AD remains unclear, particularly in relation to markers of neurodegeneration. Studying depression in individuals who carry mutations for autosomal dominant AD (ADAD) is a compelling way to characterize depressive symptoms in preclinical AD, as virtually all ADAD mutation carriers develop dementia and have a well‐characterized trajectory from pre‐symptomatic to clinical disease stages. Method: We evaluated cross‐sectional associations between the 15‐item Geriatric Depression Scale (GDS) and neurodegeneration of the hippocampus, one of the most vulnerable brain regions in ADAD and depression, in 27 cognitively unimpaired PSEN1 E280A mutation carriers and 26 matched non‐carrier family members of a Colombian kindred with ADAD. Global cognition was measured by the Mini‐Mental State Examination (MMSE); hippocampal volume was assessed by structural MRI. A general linear model with dependent variable GDS, predictor hippocampal volume, and covariates, age, sex, MMSE, and intracranial volume (ICV), was employed. Result: PSEN1 E280A carriers and non‐carriers did not differ in GDS (carriers:2.2±2.6, non‐carriers:2.9±3.5; p=0.64), sex (carriers:70% females, non‐carriers:88% females; p=0.24), age (carriers:35.9±8.2 years, non‐carriers:37.0±6.5; p=0.56), ICV (carriers:1.4 x10 6 ±1.1 x 10 5 mm 3, non‐carriers:1.4 x 10 6 ±1.3 x 10 5 mm 3 ; p=0.16), or hippocampal volume (carriers: 3867±569 mm 3, non‐carriers: 4090±371 mm 3 ; p=0.20). Compared to non‐carriers, carriers had lower MMSE scores (carriers: 28.3±2.9, non‐carriers: 29.7±0.5; p=0.03). In carriers, GDS was negatively associated with hippocampal volume (β= ‐0.71, t= ‐2.6, p=0.02), but not with age, sex, MMSE, or ICV. This association between GDS and hippocampal volume was not observed in non‐carriers (β= ‐0.26, t= ‐1.2, p=0.25). Conclusion: Depressive symptoms in cognitively‐unimpaired carriers of an ADAD mutation are significantly associated with early hippocampal neurodegeneration, years before the estimated onset of dementia. This provides some of the first evidence of a region‐specific neurodegenerative basis of depressive symptoms in preclinical ADAD. Future longitudinal investigation is needed to characterize the temporal sequence of depressive symptoms in relation to markers of brain pathology and cognitive decline in AD. Findings may have implications for early interventions to reduce depressive symptoms in individuals who have AD risk factors.